ANALISIS ANALISIS KADAR INTERLEUKIN 6 (IL-6) PADA PASIEN HEPATITIS B DI KLINIK UTAMA MATA JEC ORBITA MAKASSAR - Kasmuddin Darmo; Arlitha dekayana; Judmainnah judmainnah; Risky Nurul Fadlila RN; Amira Aznawi (Jurnal Analis Kesehatan Kendari, 2023)
ABSTRACT Hepatitis B is an inflammation of the liver caused by the hepatitis B virus. When inflammation occurs, cytokines in the body will respond or recognize the type of pathogen in the form of a virus that enters the body and Interleukin 6 (IL 6) is a cytokine secreted from tissues. body during acute or chronic infection. Interleukin 6 (IL- 6) is a proinflammatory cytokine. The purpose of this study was to analyze the levels of Interleukin 6 (IL-6) in hepatitis B patients using a descriptive analytic method. The samples used were serum samples in Hepatitis B patients as many as 20 patients who were adjusted to the inclusion and exclusion criteria using the ELISA (Enzyme Linked Immunosorbent Assay) method. The results of this study obtained that the highest interleukin 6 level was 153.67 pg/mL and the lowest interleukin 6 level was 1.37 pg/mL. Hepatitis B patients with normal interleukin 6 levels were 12 patients with a percentage of 60%, while those with high interleukin 6 levels were 8 patients with a percentage of 40%. Interleukin 6 does not cause hepatitis B but interleukin 6 and hepatitis B are related. Increased levels of interleukin 6 can be used as an indicator to predict the risk of acute hepatitis B. Keywords: Hepatitis B, Indicator, Interleukin 6 (IL-6), ELISA ABSTRAK Hepatitis B adalah peradangan pada organ hati yang disebabkan oleh virus hepatitis B. Pada saat terjadi inflamasi, sitokin yang ada dalam tubuh akan merespon atau mengenali jenis patogen berupa virus yang masuk ke dalam tubuh dan Interleukin 6 (IL 6) adalah sitokin yang disekresikan dari jaringan tubuh ketika terjadi infeksi akut atau kronik. Interleukin 6 (IL-6) merupakan sitokin proinflamasi. Tujuan dari penetilian ini adalah untuk menganalisis kadar Interleukin 6 (IL-6) pada pasien hepatitis B dengan metode deskriptif analitik. Sampel yang digunakan yaitu sampel serum pada pasien Hepatitis B sebanyak 20 pasien yang disesuaikan dengan kriteria inklusi dan ekslusi dengan menggunakan metode ELISA (Enzyme Linked Immunosorbent Assay). Hasil dari penelitian ini diperoleh kadar interleukin 6 tertinggi yaitu sebanyak 153.67 pg/mL dan kadar interleukin 6 terendah yaitu sebanyak 1.37 pg/mL. Pasien Hepatitis B dengan kadar interleukin 6 normal sebanyak 12 pasien dengan persentasi sebanyak 60%, sedangkan dengan kadar interleukin 6 tinggi sebanyak 8 pasien dengan persentasi 40%. Interleukin 6 bukan penyebab hepatitis B tetapi interleukin 6 dan hepatitis B merupakan sesuatu yang berhubungan. Meningkatnya kadar interleukin 6 bisa dijadikan indikator untuk memprediksi resiko hepatitis B akut. Kata Kunci : Hepatitis B, Indikator, Interleukin 6 (IL-6), ELISA